Synthesis and Photophysical Characterizations of Pyrroloquinolone Photosensitizers for Singlet Oxygen production1 - Sandoval-Altamirano, C (John Wiley and Sons Inc, 2023)
A series of pyrroloquinolone photosensitizers bearing different halogen substituents (Cl, Br, I) on the heterocyclic framework was studied. These structures were readily prepared through a multi-step synthetic sequence involving an oxidative protocol as an important step to access the quinolone framework. Spectroscopic characterizations and computational investigations were carried out to study the dyes before and after the oxidative step. Interestingly, the fluorescence emission was significantly reduced upon oxidation. In spite of a low photostability under UV light, the pyrroloquinolone photosensitizers proved effective to produce singlet oxygen. Higher singlet oxygen quantum yields were obtained with photosensitizers bearing halogen atoms with a higher atomic number. © 2022 The Authors. Photochemistry and Photobiology published by Wiley Periodicals LLC on behalf of American Society for Photobiology.